2014
DOI: 10.1038/srep04126
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy of single Si nanocylinders with magnetic and electric resonances

Abstract: Resonant electromagnetic properties of nanoparticles fabricated from high-index semiconductor or dielectric materials are very promising for the realization of novel nanoantennas and metamaterials. In this paper we study optical resonances of Si nanocylinders located on a silica substrate. Multipole analysis of the experimental scattering spectra, based on the decomposed discrete dipole approximation, confirms resonant excitation of electric and magnetic dipole modes in the Si nanocylinders. Influences of ligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 32 publications
0
59
0
1
Order By: Relevance
“…Recently this problem was numerically investigated for the case of cylindrical dielectric nanoparticles. 26 This paper also demonstrates that effect of substrate is more pronounced for the electric resonance. Nevertheless, for spheroid, this effect can also be compensated by tuning the aspect ratio.…”
Section: Final Results Of Optimization Is Presented Inmentioning
confidence: 72%
“…Recently this problem was numerically investigated for the case of cylindrical dielectric nanoparticles. 26 This paper also demonstrates that effect of substrate is more pronounced for the electric resonance. Nevertheless, for spheroid, this effect can also be compensated by tuning the aspect ratio.…”
Section: Final Results Of Optimization Is Presented Inmentioning
confidence: 72%
“…Figure 3 shows the numerically calculated scattering efficiency spectra (a), as well as the extinction and scattering spectra (b) of such particle. Note that the resonance frequencies of the particle can be shifted not only by changing its size, by also its shape [73,74]. Almost complete absence of conductivity currents in silicon in the optical frequency range leads to low dissipative losses, in contrast to plasmonic structures where the strong field localization is always accompanied by high dissipation.…”
Section: Optical Properties Of High-index Dielectric Nanoparticlesmentioning
confidence: 99%
“…Recently, it has been suggested that all-dielectric nanoantennas can demonstrate much better performance in nanophotonics devices [36,[53][54][55] by exploiting the magnetic Mie resonances of high-index dielectric nanoparticles [56][57][58][59]. In particular, such all-dielectric nanoantennas demonstrate enhanced radiation efficiency in contrast to their plasmonic counterparts [36,[53][54][55].…”
Section: Introductionmentioning
confidence: 99%